PENGARUH PERISTIWA PANDEMI COVID-19 TERHADAP IMBAL HASIL ABNORMAL (Studi Peristiwa pada Sembilan Sektor Emiten di Bursa Efek Indonesia) - James Andrew Hadiprajitno; Irene Rini Demi Pangestuti (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study examines the effect of the announcement first COVID-19 case in Indonesia on the abnormal returns of nine issuers' stock indices and examines government policies in preventing the spread of COVID-19 on the abnormal returns of nine issuers' stock indices. The sample used in this study consisted of nine issuer stock indexes, namely, agriculture sector, mining sector, basic industry and chemical sector, miscellaneous industry sector, consumer goods industry sector, property, real estate and building construction sector, infrastructure, utilities and transportation sector, financial sector, trade, services and investment sector in the period March 2, 2020 and March 31, 2022. The research analysis technique used is the t-test with related samples. The results stated that the announcement first COVID-19 case in Indonesia had a positive effect on the abnormal returns of nine issuers' stock indices. Meanwhile, the announcement first PSBB in Indonesia has a negative effect on the abnormal returns of 9 stock index issuers.